2022
DOI: 10.3390/jof8080800
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Fungi Alter the Acquisition of Phosphorus in Camellia oleifera through Regulating Root Architecture, Plant Phosphate Transporter Gene Expressions and Soil Phosphatase Activities

Abstract: Plant roots can be colonized by many symbiotic fungi, whereas it is unclear whether and how symbiotic fungi including arbuscular mycorrhizal fungi and endophytic fungi promote phosphorus (P) uptake in Camellia oleifera plants. The objective of the present study was to analyze the effect of inoculation with a culturable endophytic fungus (Piriformospora indica), three arbuscular mycorrhizal fungi (Funneliformis mosseae, Diversispora versiformis, and Rhizophagus intraradices), and mixture of F. mosseae, D. versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Shao et al (2021) also found that Claroideoglomus etunicatum up-regulated the expression of CsPT1 but suppressed the expression of CsPT4 in leaves of tea plants under low and appropriate P conditions. Cao et al (2022) also found that PTs expressions were dependent on the AMF species and plant tissues. It concludes that AMF-up-regulated PT expressions depend on AMF species, plant tissues, substrate P levels, and PT genes.…”
Section: Discussionmentioning
confidence: 84%
“…Shao et al (2021) also found that Claroideoglomus etunicatum up-regulated the expression of CsPT1 but suppressed the expression of CsPT4 in leaves of tea plants under low and appropriate P conditions. Cao et al (2022) also found that PTs expressions were dependent on the AMF species and plant tissues. It concludes that AMF-up-regulated PT expressions depend on AMF species, plant tissues, substrate P levels, and PT genes.…”
Section: Discussionmentioning
confidence: 84%
“…F7 (260.9 mg) was fractionated by column chromatography over Sephadex LH-20 (eluted with CH 2 Cl 2 -MeOH, 1:1) twice, followed by semi-preparative HPLC (MeOH-H 2 O, 10:90, 4 min/L) to yield Esf-36-5 compound 5 (2.7 mg, 5.495 min). CDCl 3 ): δ H 7.59 (m, 2H, H-2", 6"), 7.53 (m, 2H, H-3', 5'), 7.44 (m, 5H, H-2', 4', 6', 3", 5"), 7.36 (m, 1H, H-4"), 6.78 (s, 1H, H-6), 3.68 (s, 3H, OCH 3 -3), 3.60 (s, 3H, OCH 3 -4); 13 5). The 1 H NMR and 13 C NMR data were consistent with the literature [32].…”
Section: Isolation Of Secondary Metabolites Produced By Endophytic Fu...mentioning
confidence: 99%
“…Plant symbiotic fungi are an underexploited resource with strong scienti c novelty and potentially challenging active molecules [4]. In symbiotic fungi, endophytic fungi are organisms that reside in plant tissues without causing disease symptoms and have a signi cant impact on the host plant as they can increase plant resistance by producing a wide range of active macromolecules [5][6][7]. Symbiotic fungi such as Aspergillus fumigatus, Rhizopycnis vagum, Diaporthe maritima, and Phialophora mustea have been reported extensively to produce antimicrobial active compounds [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eluate increased the presence of Funneliformis mosseae, one of the most prevalent AM fungi able to establish a symbiotic relationship with tomato plants [45]. AMF-plant symbiosis is well-known for supporting plant growth in stress conditions [46,47] and is able to shape root architecture [48,49].…”
mentioning
confidence: 99%